Role of TL1A in Inflammatory Autoimmune Diseases: A Comprehensive Review - Xu, Wang-Dong; Li, Rong; Huang, An-Fang (Frontiers in Immunology, 2022)
TL1A, also called TNFSF15, is a member of tumor necrosis factor family. It is expressed in different immune cell, such as monocyte, macrophage, dendritic cell, T cell and non-immune cell, for example, synovial fibroblast, endothelial cell. TL1A competitively binds to receptor death receptor 3 or decoy receptor 3, providing stimulatory signal for downstream signaling pathways, and then regulates proliferation, activation, apoptosis of and cytokine, chemokine production in effector cells. Recent findings showed that TL1A was abnormally expressed in autoimmune diseases, including rheumatoid arthritis, inflammatory bowel disease, psoriasis, primary biliary cirrhosis, systemic lupus erythematosus and ankylosing spondylitis. In vivo and in vitro studies further demonstrated that TL1A was involved in development and pathogenesis of these diseases. In this study, we comprehensively discussed the complex immunological function of TL1A and mainly focused on recent findings of the pleiotropic activity conducted by TL1A in inflammatory autoimmune disease. Finish of the study will provide new ideas for developing therapeutic strategies for these diseases by targeting TL1A.